Risks, Resilience and Interdependency (Springer Nature, 2025)
This open access book is a collection of selected papers from the 3rd Tsinghua Area Studies forum by the Institute for International and Area Studies (IIAS) at Tsinghua University in Beijing, theming at “Developing Countries in the Age of Uncertainties: Risk, Resilience and Interdependency”. From the perspective of area studies, the risks faced by more fragile developing countries in an environment of uncertainty and the resilience and interdependency exhibited in the face of risks were discussed. The discussion was a brave attempt by the IIAS to inject more certainty into the uncertain world. A total of 131 papers by scholars from various countries were presented in this forum. After the forum, the editorial group of the IIAS Forum Proceedings selected ten outstanding papers and compiled them under the title “Risk, Resilience and Interdependency: Developing Countries in the Age of Uncertainty.”